Group Contests with Internal Conflict and Power Asymmetry2. (22nd April 2016) - Choi, Jay Pil; Chowdhury, Subhasish M.; Kim, Jaesoo
Abstract: We investigate simultaneous inter‐ and intra‐group conflict in the shadow of within‐group power asymmetry and complementarity in members' group‐conflict efforts. A more symmetric group faces a higher degree of internal conflict, and might expend more effort in external conflict when the group‐conflict effort technology is highly complementary. Depending on the degree of complementarity, the stronger player's relative contribution to external conflict might be higher in a more asymmetric group and, as a result, it is possible for the weaker player to earn a higher payoff. In the absence of any complementarity, the rent‐dissipation is non‐monotonic with the within‐group power asymmetry.